A compendium of developmental gene expression in Lake Malawi cichlid fishes. Issue 1 (December 2017) - Bloomquist, R.; Fowler, T.; Sylvester, J.; Miro, R.; Streelman, J.
Abstract Background Lake Malawi cichlids represent one of a growing number of vertebrate models used to uncover the genetic and developmental basis of trait diversity. Rapid evolutionary radiation has resulted in species that share similar genomes but differ markedly in phenotypes including brains and behavior, nuptial coloration and the craniofacial skeleton. Research has begun to identify the genes, as well as the molecular and developmental pathways that underlie trait divergence. Results We assemble a compendium of gene expression for Lake Malawi cichlids, across pharyngula (the phylotypic stage) and larval stages of development, encompassing hundreds of gene transcripts. We chart patterns of expression in Bone morphogenetic protein (BMP), Fibroblast growth factor (FGF), Hedgehog (Hh), Notch and Wingless (Wnt) signaling pathways, as well as genes involved in neurogenesis, calcium and endocrine signaling, stem cell biology, and numerous homeobox (Hox) factors—in three planes using whole-mountin situ hybridization. Because of low sequence divergence across the Malawi cichlid assemblage, the probes we employ are broadly applicable in hundreds of species. We tabulate gene expression across general tissue domains, and highlight examples of unexpected expression patterns. Conclusions On the heels of recently published genomes, this compendium of developmental gene expression in Lake Malawi cichlids provides a valuable resource for those interested in the relationship between evolution and development.